2021
DOI: 10.22146/jik.v15i2.1759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carrying Capacity and Conservation Scenarios of Wosi Watershed at Manokwari Regency, West Papua

Abstract: Around 12.62% of watersheds in Indonesia are damaged and need restoration immediately to prevent floods, landslides, and other related disasters. This study aimed to evaluate the Wosi watershed and formulate conservation scenarios to improve its conditions. The data collection included hydrology (quantity, continuity, and water quality), land (critical land index, percentage of vegetation cover, and erosion index), socio-economic (population pressure, welfare level, existence, and regulations enforcement), bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Impact of Watershed Characteristics on Hydrology Mahmud et al (2021a) found out that the carrying capacity of the Wosi Watershed is categorized as bad and is one of the watersheds in Manokwari Regency that must be restored. Water discharge is a very important part of hydrological parameters to evaluate the extent to which rainfall affects surface runoff, river water level, and river capacity.…”
Section: Land Usementioning
confidence: 99%
See 2 more Smart Citations
“…Impact of Watershed Characteristics on Hydrology Mahmud et al (2021a) found out that the carrying capacity of the Wosi Watershed is categorized as bad and is one of the watersheds in Manokwari Regency that must be restored. Water discharge is a very important part of hydrological parameters to evaluate the extent to which rainfall affects surface runoff, river water level, and river capacity.…”
Section: Land Usementioning
confidence: 99%
“…This shows that there is a decrease in the carrying capacity of the watershed to receive, absorb, and drain rainwater into the river. According to Mahmud et al (2021a), if the FRC is low, the water flows throughout the year without showing a significant water level. The flow of water is not only in the rainy season but continues to flow even during the dry season.…”
Section: Land Usementioning
confidence: 99%
See 1 more Smart Citation
“…Perusakan hutan merupakan masalah yang tidak bisa dibiarkan, sebagai solusi diperlukan pemahaman yang menyeluruh tentang faktor-faktor biofisik, ekonomi dan sosial (Purnomo dan Mendoza, 2011). Sebagaimana degradasi dan deforestasi hutan lindung Remu oleh pengambilan galian C berdampak banjir kota Sorong (Kompas, 2020), kerusakan dan penurunan luas hutan lindung di Bogor berdampak longsor tahun 2020 (Sidiq, 2020), penyusutan Hutan Lindung Wosi Rendani (HLWR) menjadi 88.2 ha dari semula 300.6 ha yang berdampak banjir lebih dari satu kali dalam setahun (Mahmud et al, 2021).…”
Section: Pendahuluanunclassified
“…Padahal kawasan semua itu masuk HLWR bagian dari DAS Wosi, sehingga tidak heran saat ini hutan hanya tersisa 26%. Menurut Mahmud et al (2021) daya dukung DAS Wosi berkategori buruk dan sangat buruk yang dikategorikan sebagai DAS yang harus dipulihkan. Begitu juga DAS Wosi merupakan salah satu dari tujuh DAS yang harus dipulihkan berada dalam ibu kota Provinsi Papua Barat (BPDASHL Remu Ransiki, 2016).…”
Section: Sedimenunclassified